Using telemedicine for a lower carbon footprint in healthcare: A twofold tale of healing - Christos Tsagkaris; Anastasiia V. Hoian; Shoaib Ahmad; Mohammad Yasir Essar; Loyle Wesley Campbell; Lena Grobusch; Theodoros Angelopoulos; Konstantinos Kalaitzidis (Elsevier, 2021)
The carbon footprint associated with healthcare has recently raised concerns about how medical practice can be made more sustainable. At the same time, Telemedicine has grown enough to enable medical practitioners to provide reliable healthcare services remotely. The propagation of telehealth amid the COVID-19 pandemic serves as an opportunity to work more consistently towards lowering healthcare's carbon footprint by decreasing transportation and other carbon-emitting activities. Efforts in research methodology, medical education and policy are necessary to further investigate how it can contribute to lowering the footprint of the healthcare sector.